2017
DOI: 10.3892/etm.2017.4913
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the bladder epithelial barrier are associated with ketamine-induced cystitis

Abstract: The aim of the present study was to investigate the changes of the bladder epithelial barrier in the pathogenesis of ketamine-induced cystitis (KIC). A total of 60 female mice were randomly allocated into control and ketamine groups, which received daily intraperitoneal injections of saline and ketamine, respectively. Micturition behavior was recorded in 2-h intervals at the end of 4, 8 and 12 weeks, and bladders were harvested for subsequent analyses. Routine hematoxylin and eosin staining was performed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…The present results suggested that high-dosage long-term ketamine administration promoted inflammatory cell infiltration and vascular congestion in the submucosal layer of the bladder, which were observed in patients with long-term ketamine abuse ( 39 , 40 ). Although the induced inflammatory response was not present in all mice, the pathological outcome was consistent with previous studies using an identical mouse strain, C57BL/6, and a similar ketamine regimen, 100 mg/kg/day ( 10 , 41 ). However, previous studies performed on rat models identified a pronounced and consistent inflammatory response ( 7 , 42 ).…”
Section: Discussionsupporting
confidence: 89%
“…The present results suggested that high-dosage long-term ketamine administration promoted inflammatory cell infiltration and vascular congestion in the submucosal layer of the bladder, which were observed in patients with long-term ketamine abuse ( 39 , 40 ). Although the induced inflammatory response was not present in all mice, the pathological outcome was consistent with previous studies using an identical mouse strain, C57BL/6, and a similar ketamine regimen, 100 mg/kg/day ( 10 , 41 ). However, previous studies performed on rat models identified a pronounced and consistent inflammatory response ( 7 , 42 ).…”
Section: Discussionsupporting
confidence: 89%
“…ZO-1 has been accepted as a specific and sensitive biomarker for IC patients [ 24 ]. In a ketamine-induced IC model, Duan et al [ 25 ] detected that the abnormal distribution of ZO-1 proteins after 8 weeks was 90%, as opposed to 0% in the control group. We showed that abnormal expression of ZO-1 was significantly higher in group II than in groups I, III, and V.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelium barrier dysfunction is proposed as a major mechanism in the pathogenesis of KC 12,14‐16,21 . The barrier function comprises multiple defensive molecules including glycosaminoglycans (GAGs), uroplakin plaques, and tight and adherent junctions 15,22 .…”
Section: Urothelium Disruptionmentioning
confidence: 99%
“…Previous studies reported that a contracted bladder with urothelium denudation and lamina propria fibrosis and inflammation were the common pathological features 10‐12 . The urothelium is in direct contact with ketamine and its metabolites in the urine, and has been shown to suffer a loss of junction proteins such as zonula occludens (ZO)‐1 and E‐cadherin and to become more apoptotic 13‐16 . Based on these findings and the urothelium pathological features, urothelial barrier dysfunction has been indicated as the major pathogenesis of KC.…”
Section: Introductionmentioning
confidence: 99%